Communication Training, Adverse Events, and Quality Measures: 2 Retrospective Database Analyses in Washington State Hospitals. Issue 5 (August 2021) - Slade, Ian R.; Beck, Sara J.; Kramer, C. Bradley; Symons, Rebecca G.; Cusumano, Michael; Flum, David R.; Gallagher, Thomas H.; Devine, Emily Beth
Abstract : Objective: Washington State's HealthPact program was launched in 2011 as part of AHRQ's Patient Safety and Medical Liability Reform initiative. HealthPact delivered interdisciplinary communication training to health-care professionals with the goal of enhancing safety. We conducted 2 exploratory, retrospective database analyses to investigate training impact on the frequency of adverse events (AEs) and select quality measures across 3 time frames: pretraining (2009–2011), transition (2012), and posttraining (2013). Methods: Using administrative data from Washington State's Comprehensive Hospital Abstract Reporting System (CHARS) and clinical registry data from the Surgical Care and Outcomes Assessment Program (SCOAP), we compared proportions of AEs and quality measures between HealthPact (n = 4) and non-HealthPact (n = 93-CHARS; n = 48-SCOAP) participating hospitals. Risk ratios enabled comparisons between the 2 groups. Multivariable logistic regression enabled investigation of the association between training and the frequency of AEs. Results: Approximately 9.4% (CHARS) and 7.7% (SCOAP) of unique patients experienced 1 AE or greater. In CHARS, the odds of a patient experiencing an AE in a HealthPact hospital were initially (pretraining) higher than in a non-HealthPact hospital (odds ratio [OR], 1.13; 95% confidence interval [CI], 1.10–1.17), lower in transition (OR, 0.80; 95% CI, 0.76–0.83) and posttraining (OR, 0.72; 95% CI, 0.69–0.75) periods. In SCOAP, ORs were consistently lower in HealthPact hospitals: pretraining (OR, 0.87; 95% CI, 0.80–0.95), transition (OR, 0.75; 95% CI, 0.70–0.81), and posttraining (OR, 0.63; 95% CI, 0.58–0.68). The proportion of at-risk patients that experienced each individual AE was low (<1%) throughout. Adherence to quality measures was high. Conclusions: Interprofessional communication training is an area of intense activity nationwide. A broad-based training initiative may play a role in mitigating AEs. Abstract : Supplemental digital content is available in the text.